1986
DOI: 10.1177/002221948601900207
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence and Behavioral Problems of Learning Disabled Boys Aged 12–-16

Abstract: Parents' reports on social competence and behavioral problems were obtained for 53 learning disabled boys 12-16 who were referred for a psychoeducational assessment at the Center for Disorders of Communication at the University of Vermont. One parent of each boy completed the Child Behavior Checklist developed by Achenbach and Edelbrock (1983). On average, the LD boys showed significantly lower levels of social competence and more behavior problems compared to normative samples of boys in the same age range. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…McConaughy (1986) and McConaughy and Ritter (1986) reported that boys with LD experienced significantly more problem behaviors on the CBCL than nonreferred boys. Ellen (1989) compared groups of students with LD, SED, and no handicapping conditions on a scale that measured acting-out, learning problems, and shy-anxious behavior.…”
mentioning
confidence: 99%
“…McConaughy (1986) and McConaughy and Ritter (1986) reported that boys with LD experienced significantly more problem behaviors on the CBCL than nonreferred boys. Ellen (1989) compared groups of students with LD, SED, and no handicapping conditions on a scale that measured acting-out, learning problems, and shy-anxious behavior.…”
mentioning
confidence: 99%
“…Others have found that children with specific learning disabilities exhibit increased levels of anxiety, withdrawal, depression, and low selfesteem when compared to nonhandicapped children (Eliason & Richman, 1988;McConaughy, 1986;McConaughy & Ritter, 1986;Rosenthal, 1973). Researchers have also documented that, compared to their normally achieving peers, children with specific learning disabilities are less well liked and more likely to be rejected by others (Bruininks, 1978;Bryan, 1976;Garrett & Crump, 1980;Gresham & Reschly, 1986;Morrison, 1981;.…”
mentioning
confidence: 99%
“…The frustration of prolonged failure on a range of academic subjects would result in feelings of anxiety and insecurity (Boetsch, Green, & Pennington, 1996; Richman, Stevenson, & Graham, 1982), which may in turn pose profound negative influence upon these individuals’ self-image (Burden, 2005; Humphrey & Mullins, 2002; Undheim, 2003), emotions (Beitchman & Young, 1997; Boetsch et al, 1996; Heiervang, Stevenson, Lund, & Hugdahl, 2001), as well as acceptance and adjustment among peers (Bender & Wall, 1994; Hellendoorn & Ruijssenaars, 2000; LaGreca & Stone, 1990). In dealing with problems, some dyslexic individuals may release their tensions through aggressive and antisocial behavior (McConaughty, 1986; McKinney, 1989; McKinney & Feagans, 1984; Sanson, 2006).…”
Section: Bcl-jsmentioning
confidence: 99%